Alkenyl Arenes as Dipolarophiles in Catalytic Asymmetric 1, 3‐Dipolar Cycloaddition Reactions of Azomethine Ylides. Issue 49 (11th November 2016) - Pascual‐Escudero, Ana; de Cózar, Abel; Cossío, Fernando P.; Adrio, Javier; Carretero, Juan C.
Abstract: The use of alkenyl arenes as dipolarophiles in the catalytic asymmetric 1, 3‐dipolar cycloaddition of azomethine ylides is reported. Under appropriate reaction conditions with a Cu I or Ag I catalyst either the exo or the endo adduct was obtained with high stereoselectivity. This process provides efficient access to highly enantiomerically enriched 4‐aryl proline derivatives. The observed results are compatible with the blockage of one prochiral face of the 1, 3‐dipole, as well as with the efficient transmission of electrophilicity towards the terminal carbon atom of the dipolarophile. This polarization results in a change from a concerted to a stepwise mechanism. Abstract : One is enough : A single electron‐withdrawing group on the aryl moiety was sufficient for the efficient metal‐catalyzed title reaction. Depending on the catalytic system used, either the exo or the endo 4‐aryl pyrrolidine product was formed preferentially (see scheme). DFT calculations revealed that electronic effects in the styrene substrate play a key role in the reaction mechanism.